The TGF-β superfamily as potential therapeutic targets in pancreatic cancer - Tindall, Rachel R.; Bailey-Lundberg, Jennifer M.; Cao, Yanna; Ko, Tien C. (Frontiers in Oncology, 2024)
The transforming growth factor (TGF)-β superfamily has important physiologic roles and is dysregulated in many pathologic processes, including pancreatic cancer. Pancreatic cancer is one of the most lethal cancer diagnoses, and current therapies are largely ineffective due to tumor resistance and late-stage diagnosis with poor prognosis. Recent efforts are focused on the potential of immunotherapies in improving therapeutic results for patients with pancreatic cancer, among which TGF-β has been identified as a promising target. This review focuses on the role of TGF-β in the diseased pancreas and pancreatic cancer. It also aims to summarize the current status of therapies targeting the TGF-β superfamily and postulate potential future directions in targeting the TGF-β signaling pathways.